The significance of natural and serene environment to improve the quality of living in tiny living spaces / Murni Zainal and Azhan Abdul Aziz - Zainal, Murni; Abdul Aziz, Azhan (2021)
Malaysia’s average house size is shrinking and living in the city also has many negative aspects ranging from overcrowding & overpriced housing. Therefore, the demand for having natural and serene environments to the living space has increased. The objectives of the study are to investigate the benefits of exploiting nature and serenity in promoting a supportive environment for achieving user well-being. Qualitative and quantitative methodologies were applied using three case studies (CS1: Prototype Model of Microhouse at Medan Pasar, Kuala Lumpur, CS2 at Sub urban area: The Cabin Boutique Resort at Pantai Remis, Kuala Selangor and CS3 at Outskirts area: Meraki Tiny House at Behrang). The tool, Perceived Sensory Dimensions “(PSDs)” was used to observe the environment and it’s tiny living spaces by taking significant photos of two sensory dimension models (PSDs Nature and Serene). Close-ended questionnaires are distributed to the potential users to rate the perception for each case study. The results have shown that a natural and serene environment for CS3 is the most preferred because of the aspirational quality of its PSDs. This is followed by CS2, while CS1 only showed the appropriate quality of its PSDs.